SPECIFICITY OF GEOGRAPHICAL CONTENT FOR THE APPLICATION OF DEBATE IN GEOGRAPHY LESSONS - Đorđević, Ivana (Bulletin of Natural Sciences Research, 2025)
Modern geography teaching involves a more intensive use of methods designed to encourage students to learn with reason, to think reasonably and to draw independent conclusions. One of the methods that can contribute to achieving the above goals is certainly the use of debate and its increased implementation in geography lessons. Debating is a form of dialogic method that involves a discussion between two teams and the exploration of a given topic through argumentative practice. The paper analyzes the content of geography lessons that can be learned through debating and its application in the classroom from a theoretical and practical perspective. The first part of the paper is devoted to the theoretical foundations of teaching methods, the conceptual definition of debate, the Karl Popper format and the rules that should be applied in classroom practice. The second part of the paper deals with the application of debate in geography lessons using a content analysis with concrete examples from the subject. The results of the paper show the importance of debate for the development of skills that students in Serbia lack, including argumentative reasoning, public speaking, collaboration and research skills.
Keywords: Teaching methods; Debate; Karl Popper; Geography lessons; Logical thinking